The case of a 2-year-5-month-old boy with aseptic meningitis caused by Enterovirus 71 - Jirasakpisarn, Suwadee; Na Ayuthaya, Satja Issaranggoon; Oberdorfer, Peninnah (Biomedical Sciences and Clinical Medicine, 2024)
Aseptic meningitis is caused predominantly by non-polio human enteroviruses, including Enterovirus 71 (EV71). Physicians who treat children with aseptic meningitis should always consider the possibility of EV71 causing infection, even without the presence of skin and mucocutaneous lesions. The authors report the case of a 2-year-5-month-old boy who presented with high-grade fever, vomiting and developed seizure. A cerebrospinal fluid test and magnetic resonance imaging of his brain revealed that he had aseptic meningitis. Supportive treatment and various antibiotics were prescribed at first, but the fever persisted. Finally, a polymerase chain reaction (PCR) test of his stool found that the causative agent was EV71. The patient stayed in hospital for 17 days and fully recovered without any neurological deficits.